Projeto de sistema de aquisição de dados e controle de motogerador a biogás via programação por diagrama de blocos - Diniz, Pedro Henrique Santiago (2017)
The eletrical energy microgeneration from generating set has been widely applied, in general, using diesel fuel. However, biogas is an interesting alternative in the generating system operation, because it is a renewable energy source, emits less pollutants, has great potential to be explored, among other advantages. The search for efficient generating set occurrs through the automation technologies implementation, based on data acquisition and control systems. Thus, the study objective is design a data acquisition and control system for a test room biogas generating set on the Laboratory of Combustion and Renewable Energies (LACER) on the Department of Mechanical Engineering on the UFC. The tests planning contemplates practical operation situations simulating real field conditions to enable the power generation measurement from the use of biogas in different methane concentrations. Then, the instrument specification was made, which includes differents sensors and actuators that will be installed in the generating set, as well the hardware and software for data acquisition and control specification was made too. The manufacturing company chosen to supply the data acquisition and control system is National Instruments, which uses LABVIEW software, whose wide programming versatility allows appropriate measurement rates for each instrument. As a result, we have all instruments, actuators and modules I/O specifications and a block diagram code that enables the data acquisition and control, which includes the discreet resistance management.